(2/3+2/9+2/27+2/81)-(1/2+1/4+1/8+1/16)
人气:347 ℃ 时间:2020-05-14 14:32:18
解答
(2/3+2/9+2/27+2/81)-(1/2+1/4+1/8+1/16)
=(54/81+18/81+6/81+2/81)-(8/16+4/16+2/16+1/16)
=80/81-15/16
=(1-1/81)-(1-1/16)
=1/16-1/81
=65/1296
推荐
- 1+3分之2+9分之4+27分之8+81分之16+243分之32+729分之64
- (1/2)^(1/3) * (1/4)^(1/9)* (1/8)^(1/27)*(1/16)^(1/81). = ? 要过程!
- [1.9+1.9*(4.8-3.81)]/(2.9-2.8)
- 2/3+2/9+2/27+2/81
- 1/2,3/4,8/9,( ),81/32,( ),( ) 27/64,9/16,3/4,( ),( ) 找规律
- 数列2,3,8,29,()
- He will have his car repaired next week.求翻译
- 设a∈R,若函数y=eax+3x,x∈R有大于零的极值点,则( ) A.a>-3 B.a<-3 C.a>-13 D.a<-13
猜你喜欢